Role of fault attributions and desire/effort/outcome expectations in children’s anticipated responses to hypothetical peers with various undesirable characteristics - Barnett, Mark A.; Sonnentag, Tammy L.; Livengood, Jennifer L.; Struble, Adrienne L.; Wadian, Taylor W. (My University, 2011)
A total of 137 third- through eighth-grade students were asked to respond to a series of statements concerning six male peers described as having various undesirable characteristics (i.e., poor student, poor athlete, extremely overweight, extremely aggressive, extremely shy, or having the symptoms of ADHD). The aggressive peer and the overweight peer consistently elicited the least favorable reactions from the children. For all six peers included in the study, the more strongly the children agreed that a peer was at fault for his undesirable characteristic, the less favorably they anticipated responding to that peer. In contrast, the children’s expectations concerning a peer’s desire to change, effort to change, and success in changing an undesirable characteristic were generally unrelated to their anticipated responses to that peer. The children demonstrated the general belief that desire backed by effort leads to success in overcoming an undesirable characteristic, but lack of effort leads to failure regardless of the peer’s desire or lack of desire to change the characteristic.
Keywords: Desire/effort/outcome expectations; Fault attributions; Peer evaluation; Social cognition